An Extreme Value Analysis Of The Sea Level At Axim - Opoku, E. (University of Ghana, 2019)
Assessing the probability of the sea level rising because of heavy rains and tidal waves is an important issue to engineers and coastal development planners. In the case of Axim, the sea level rise leads to flooding, loss of lives and the destruction of properties in communities such as Brawie, upper and lower Axim. This has led to the commencement of a sea defence project in Axim to protect the community from floods and further destruction of properties. The data used in this study were hourly sea level data from the Axim sea spanning the period January 1980 to January 2019. In this study, we used Extreme Value Theory (EVT) to estimate the exceedance probabilities and return periods of high sea levels that can result in flooding and its associated effects. The study began with an assessment of the domain of attraction of the tails of the Axim sea level data. The Generalised Pareto distribution (GPD) was used to fit the excess data above a chosen high threshold. The Probability Weighted Moment (PWM) and Maximum Likelihood (ML) methods were used to estimate the shape parameter 𝛾 of the GPD. The study showed that the tail distribution of the Axim sea level data is in the Weibull domain of attraction, that is, it has a negative shape parameter (𝛾<0). Also, the study revealed that the probability of the sea exceeding the maximum observed data of 1.83 meters (above mean sea level) is 0.0031. Finally, the study concluded that based on theory and data at hand, there is a negligible chance of the Axim sea rising above 2 meters.
MPhil. Statistics
Keywords: Axim sea; Ghana; maximum; Pareto distribution; flooding